A profile of sports science research (1983-2003) - Williams, S. J.; Kendall, L. R. (Journal of Science and Medicine in Sport, 2007)
A majority of sports science research is undertaken in universities and dedicated research centres, such as institutes of sport. Reviews of literature analysing and categorising research have been carried out, but categories identified have been limited to research design and data gathering techniques. Hence there is a need to include categories such as discipline, subjects and targeted sport. A study was conducted using document analysis method to gather data that described and categorised performance-based sports science research projects in Australian universities and institutes of sport. An instrument was designed that could be used by researchers to analyse and profile research in the area of sports science. The instrument contained six categories: targeted sport, primary study area, participant type, research setting, methodology and data gathering techniques. Research documents analysed consisted of 725 original unpublished research reports/theses. Results showed that over two-thirds of research projects were targeted to specific sports and, of this group, nearly half involved four sports: cycling, rowing, athletics and swimming. Overall, physiology was the most researched scientific discipline. The most frequently used research method was experimental design, and the most frequently used data gathering technique was physiological (performance) measures. Two-thirds of research was conducted in laboratory settings, and nearly half of the research was conducted with elite or sub-elite athletes as participants/subjects. The findings of this study provide an overall synopsis of performance-based sports science research conducted in Australia over the last 20 years, and should be of considerable importance in the ongoing development of sports science research policy in Australia.